Plan de Gestión de Riesgos Proyecto Hidroeléctrico Capulín-San Pablo - Montalto-Cruz, Adrián (Instituto Tecnológico de Costa Rica, 2015)
This document corresponds to the development of a risk management plan for the Hydroelectric Project Capulín - San Pablo. Through which the current situation of the company in risk management was analyzed in order to establish a methodology to determine the risks that may affect the project, documenting their characteristics and prioritize which of these risks require a plan of action. So we can address the risks in order depending on the severity that these have for the project. This was achieved by consulting the professionals in charge of the work, which contributed with the identification, and the evaluation of the risks. Having risks with a degree of low, medium or high importance, the latter being the most important because of the effect they may have on the project objectives. A computer program was performed by Visual FoxPro 9.0 which is capable of performing this assessment by entering the relevant information. Also, this program is able to display a list of registered risks and matrix: cause - effect, and operational risk. So it was through this tool that 41 risks were obtained, of which 3 are opportunities and 38 threats. Where 18 risks have a high degree so they were assigned a measure of action in order to correct or seize the potential impact they may have on the project.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Riesgo; Matriz; Probabilidad; Impacto; Control